Art therapy - Edwards, David G. 1954- (Los Angeles SAGE, 2014)
"Brings theory to life through case material and examples of real artwork produced during therapy sessions. Practising art therapist Dave Edwards explains key theoretical ideas - such as symbolism, play, transference and interpretation - and shows how these relate to practice."--Provided by publisher.
What is art therapy? -- The historical background to art therapy -- The emergence of art therapy as a profession in the UK -- Frames of references : psychoanalysis, art and art therapy -- Art therapy in practice -- Training : from apprentice to practitioner -- Professional issues.
Includes bibliographical references (pages 164-186) and index.
Keywords: Art therapy; Arts -- Therapeutic use